STUDI ETNOBOTANI DAN AKTIVITAS FARMAKOLOGI EKSTRAK DAUN SIRSAK (Annona Muricata L.) - Rasyidah Rasyidah (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2019)
Annona muricata L. is a medicinal plant and claimed to be useful for human health. Study of ethnobotany about this plant need more research in order to find a range of pharmacological properties. Exploration of chemical constituents for soursop leaf extract is reported and contain numerous complex active phytochemicals. These secondary metabolite were important to explore more pharmacology activity. Leaf of Annona muricata L. had extracted and had been identified to has benefecial effects as anticancer, antioxidant, antiinflammatory, antihyperglicaemic, antifungal, and antibacterial. This review research emphasizes the systematic investigation of Annona muricata L. in pharmacology activity, which could be the impotent source for numerous human disorders. The result showed that 6 pharmacology activity from this leaves exctract which are anti-cancer, antioxidant, anti-inflammatory , antihyperglycemic, antifungal and antibacterial.Keywords: soursop leaf, Annona muricata, pharmacology